Apparent timing and duration of the Matuyama‐Brunhes geomagnetic reversal in Chinese loess. (28th November 2014) - Zhao, Hui; Qiang, Xiaoke; Sun, Youbin
Abstract The Matuyama‐Brunhes (MB) geomagnetic reversal in Chinese loess has been studied extensively as an important boundary for land‐ocean stratigraphic and paleoclimatic correlations. However, the apparent timing and duration of the MB boundary remain controversial in Chinese loess deposits due to its inconsistent stratigraphic position and the uncertain chronologies. Here we synthesized high‐resolution paleomagnetic records from four loess sequences in the central Chinese Loess Plateau and synchronized the loess‐paleosol chronology by matching the grain‐size variations to orbitally tuned grain‐size time series. The synthesized paleomagnetic results reveal consistent features of the MB transition in Chinese loess, including the stratigraphic position (L8/S8 transition), timing (∼808–826 ka), duration (∼14–16 ka), and rapid directional oscillations. Compared with the MB transition in marine records (770–775 ka), the timing of the MB transition is relatively older and longer in Chinese loess, due to a complex interplay between different remanence acquisition mechanisms which occurred during the course of postdepositional physical and chemical processes.